PERLINDUNGAN HUKUM TERHADAP KONSUMEN PENGGUNA KOSMETIK YANG MENGANDUNG BAHAN BERBAHAYA - Reinhard Bungaran Nathanael, (2024)
Cosmetics can be said to be one of the daily necessities needed by humans, especially women. Until now, there are many different types of cosmetic products circulating on the market and have different properties for human skin. However, in reality it is not as imagined, because, in fact, there are still many cosmetics that contain dangerous ingredients and irresponsible individuals produce and sell these cosmetics on the market. So in this problem consumer protection is required to be able to help consumers in solving problems experienced by consumers who have been affected by cosmetics that contain dangerous ingredients. The aim of this research is to find out the form of legal protection for consumers who use cosmetics that contain free dangerous ingredients as well as the accountability of authorized bodies in supervising the distribution of cosmetics that contain dangerous ingredients. The author uses a type of juridical-normative research through literature study, with an approach to statutory regulations and other legal materials related to the problems to be discussed as well as searching the websites of authorized government institutions and searching on the internet. The author hopes that the results of this research will be able to have a significant impact in efforts to educate the public, especially those who still do not know about cosmetics that contain dangerous ingredients and the legal system that can be followed by consumers if cosmetics containing dangerous ingredients are still found to be sold freely.